Pengaruh Penyuluhan Terhadap Pengetahuan Sikap Perilaku Kader PKK Kelurahan Sukagalih Kota Bandung Tentang Diabetes Mellitus - Kartika Suhada; Cindra Paskaria; Meilinah Hidayat; Audyati Gany (Institute for Research and Community Service in Universitas Yudharta Pasuruan, 2019)
Diabetes Mellitus is a chronic metabolic disorder which is a serious problem for the health of the people of Indonesia and the world, so the International Diabetes Federation (IDF) and the World Health Organization (WHO) set November 14 as World Diabetes Day. The aim of the research is to increase public knowledge about Diabetes Mellitus, to behave and behave as they should in their daily lives, starting with lifestyle and patterns of food and drink intake. Counseling is carried out to PKK cadres as the spearhead who continue to the community members. The study design was a lecture accompanied by cross sectional pre and post test data collection. The results of the knowledge aspects of the study showed that there was a very significant difference between the pre and post test results (p = 0,000). The attitude aspect showed that there was no significant difference between the pre and post test results (p = 0.257), but overall the cadre's attitude regarding a healthy lifestyle to prevent Diabetes Mellitus was good enough. Behavioral aspects indicate that there are respondents who behave well, a maximum value of 3, but some are not good, a minimum value of 0. The results of blood sugar tests when showing as many as 69.57% of participants are not certain to have DM, while the rest are not DM. The conclusion is that there is a very significant increase in PKK cadre knowledge, but there has not been a significant change in attitude after attending counseling.